2003
DOI: 10.1038/nm822
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Tat reprograms immature dendritic cells to express chemoattractants for activated T cells and macrophages

Abstract: Immature dendritic cells are among the first cells infected by retroviruses after mucosal exposure. We explored the effects of human immunodeficiency virus-1 (HIV-1) and its Tat transactivator on these primary antigen-presenting cells using DNA microarray analysis and functional assays. We found that HIV-1 infection or Tat expression induces interferon (IFN)-responsive gene expression in immature human dendritic cells without inducing maturation. Among the induced gene products are chemokines that recruit acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
151
3
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 198 publications
(168 citation statements)
references
References 45 publications
11
151
3
3
Order By: Relevance
“…Indeed, although human DC that are generated in vitro do not mature after infection by HIV (this phenomenon might be actually due to some interference of HIV proteins with the DC maturation pathways [40]), plasmacytoid DC, which can be activated by stabilized RNA (B. Scheel, ongoing studies), mature in contact with infectious or heat-inactivated HIV. Activation of plasmacytoid DC by HIV indicates that this virus contains a PAMP and, on the basis of our data, we postulate that this PAMP is the stabilized RNA genome of the retrovirus.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although human DC that are generated in vitro do not mature after infection by HIV (this phenomenon might be actually due to some interference of HIV proteins with the DC maturation pathways [40]), plasmacytoid DC, which can be activated by stabilized RNA (B. Scheel, ongoing studies), mature in contact with infectious or heat-inactivated HIV. Activation of plasmacytoid DC by HIV indicates that this virus contains a PAMP and, on the basis of our data, we postulate that this PAMP is the stabilized RNA genome of the retrovirus.…”
Section: Discussionmentioning
confidence: 99%
“…Poluektova et al (21) showed induction of CXCL10 and CXCL9 in MDM, but did not investigate the requirements for chemokine induction. Izmailova et al (19) showed the induction of multiple chemokines in a chip-based screen of gene expression, including CXCL10, CXCL9, and CCL8 by HIV infection of MDDC in vitro, which they attributed to the activity of Tat. Interpretation of these data was complicated, however, by the lack of correspondence in the time courses of accumulation of Tat and chemokines and by the use of an adenovirus vector to express Tat in MDDC, which, based on the data discussed below (44), might have influenced expression of the CXCL10 gene.…”
Section: Figurementioning
confidence: 99%
“…Even the related, third CXCR3 ligand, CXCL9, which was reported recently to be induced by HIV-1 (19,21), is highly dependent for its induction on IFN-␥ both in vitro (52) and in vivo (53), so that induction in the absence of cells producing IFN-␥ would be expected to be minimal. In line with our real-time PCR data, when we used the conditioned medium from infected vs uninfected MDM in a chemotaxis assay with CD4 ϩ T cells, all HIV-1-induced chemotactic activity could be blocked by Ab neutralization of CXCR3, indicating that none of the non-CXCR3 chemokines was contributing.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations